Pengaruh Produk Domestik Bruto Riil, Nilai Tukar dan Tingkat Suku Bunga Riil Terhadap Inflasi di Indonesia Periode 1994-2013 - Sarwedi Alamsyah; Anthony Mayes; Rosyetti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
One of the problems in almost all countries in the world is the difficulty of maintaining the stability of the economy. Various policies, both fiscal policy and monetary policy carefully planned and then carried out to obtain the various targets of economic growth is expected to bring prosperity to the community. One of the efforts the fulfillment of the economic growth target is done by controlling the rate of inflation, both at regional and at national level. The inflation rate in the right figure is able to bring the economy towards positive growth. The purpose of this study was to determine the effect of the Gross Domestic Product (GDP) real exchange rate and real interest rates on inflation in this Indonesia.Penelitian using secondary data types. Analysis method used is the method of quantitative analysis using multiple regression analysis SPSS version 18.0. Results show the results of research conducted simultaneous real gross domestic product, the exchange rate, and real interest rates have a significant effect terhadapinflasi inflation in Indonesia for the period 1994-2013 with F 0.000 and 125.606 with sig R2sebesar value 0.952 which means 95.2% Inflation in Indonesia is influenced by real gross domestic product, the exchange rate, and the rate of the real man, while the remaining 4.8% is influenced by other factors not addressed in this study.Keywords: Gross Domestic Product (GDP) of the Rill, Exchange Rate, Real Interest Rate, Inflation.